2015
DOI: 10.1590/0100-67622015000500012
|View full text |Cite
|
Sign up to set email alerts
|

ANÁLISE SILVICULTURAL E ECONÔMICA DE PLANTIOS CLONAIS E SEMINAIS DE Tectona grandis L.f. EM SISTEMA TAUNGYA1

Abstract: RESUMO -O objetivo deste estudo foi realizar uma análise silvicultural e econômica de plantios clonais e seminais de Tectona grandis em monocultivo e em sistema taungya com Zea mays, no Município de Figueirópolis D'Oeste, MT. O experimento foi instalado em 2010 e compôs um fatorial 2x2 em blocos casualizados e quatro repetições. Avaliaram-se a altura total (H), o diâmetro a 5 cm (DAB) e a 1,3 m (DAP) de altura em relação ao nível do solo, a área basal, o volume, a sobrevivência e a estimativa e tendência de cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
0
3
0
12
Order By: Relevance
“…For the same spacing, the asymptotes of the equations (Table 2), as well as mean square diameter ( Figure 1) and average volume with bark per plant (Figure 2), were greater for teak grown in the Inceptisol than in the Oxisol. Although the Inceptisol is more restrictive to teak cultivation (Medeiros, 2016) due to the occurrence of rock fragments in the soil mass (Santos et al, 2013), plant growth can be benefited by the nutrient reserves present in the soil, as observed by Tonini et al (2009) and Medeiros et al (2015). In addition, teak requires soils with higher phosphorus content and base saturation (Favare et al, 2012), and does not tolerate the presence of hydrogen and aluminum (Pelissari et al, 2014a(Pelissari et al, , 2014b, which were found in the Inceptisol evaluated in this work (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…For the same spacing, the asymptotes of the equations (Table 2), as well as mean square diameter ( Figure 1) and average volume with bark per plant (Figure 2), were greater for teak grown in the Inceptisol than in the Oxisol. Although the Inceptisol is more restrictive to teak cultivation (Medeiros, 2016) due to the occurrence of rock fragments in the soil mass (Santos et al, 2013), plant growth can be benefited by the nutrient reserves present in the soil, as observed by Tonini et al (2009) and Medeiros et al (2015). In addition, teak requires soils with higher phosphorus content and base saturation (Favare et al, 2012), and does not tolerate the presence of hydrogen and aluminum (Pelissari et al, 2014a(Pelissari et al, , 2014b, which were found in the Inceptisol evaluated in this work (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Contudo, esse maior crescimento também pode estar relacionado ao fato do T4 ser um monocultivo. Medeiros et al (2015) avaliando o crescimento de Tectona grandis L.F. em sistemas consorciados, verificaram que as plantas crescem mais no monocultivo devido ao fato de estarem livres de competição interespecífica.…”
Section: Discussionunclassified
“…En Brasil, para el año 2013, existían aproximadamente unas 60.000 ha de teca plantadas principalmente al sur de la región de Mato Grosso, representando la mayor superficie de plantación de esta especie en América Latina. Las técnicas de multiplicación vegetativa han permitido la instalación de algunas plantaciones clonales de teca y ensayos para la evaluación de su productividad (Medeiros et al, 2015). En países como Canadá, donde las coníferas representan las principales especies comerciales, las nuevas técnicas de clonación han resultado una herramienta importante para la multiplicación de los genotipos de interés.…”
Section: Ejemplos De Plantaciones Forestales Clonalesunclassified